Assessment of the Level and Health Risk of Fluoride and Heavy Metals in Commercial Toothpastes in Bangladesh - Chanchal Chayan Paul; Md. Abu Shamim Khan; Probir Kumar Sarkar; Abdul Hakim; Md. Waliullah; Bablu Hira Mandal (Indonesian Journal of Chemistry, 2020)
Toothpaste is one of the daily essentials, and good quality control practices over it are very important to protect the oral public health from adverse effects. The current study aimed to assess the concentration of fluoride and heavy metals, physicochemical properties in ten different toothpaste samples in Bangladesh, followed by related health risk analysis. pH, moisture content, F–, As, Cu, Pb contents were measured by membrane electrode, thermogravimetric, SPADNS, HG-AAS, flame-AAS methods, respectively. The results were compared to the specification of the packet and Bangladesh Standard and Testing Institute (BSTI) standard. The physicochemical properties well-matched the formulation standard values. The moisture content was 27.18 ± 2.20 to 52.10 ± 5.01%, with 50% of the samples in permissible limit but the pH of all the samples (6.40-8.60) was within the standard limit. Available F–, Cu, Pb, and As content ranged from 803–1617, 2.78–13.10, 0.27–2.12, and 0.027–0.637 mg/Kg, respectively. F– content in 80% toothpaste did not meet the packet specification and was higher than BSTI standard, though heavy metals were within the BSTI limit. Hazard quotient (HQ) and HI (Hazard Index) analysis revealed that toothpaste safe from heavy metal related to health risk.